2009
DOI: 10.1097/yct.0b013e318199f767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Remifentanil on Convulsion Duration and Hemodynamic Responses During Electroconvulsive Therapy

Abstract: Remifentanil (1 microg/kg) administered before thiopental (1 mg/kg) has no adverse effect on the duration of ECT-induced convulsion and recovery time, but it can attenuate the increase in heart rate and arterial blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…7,8 Propofol is a short-acting hypnotic agent, chemically distinct from barbiturates, that is widely used for general anesthesia for operative procedures, as well as for ECT. Other agents that are frequently used for ECT include thiopental, ketamine, and etomidate.…”
mentioning
confidence: 99%
“…7,8 Propofol is a short-acting hypnotic agent, chemically distinct from barbiturates, that is widely used for general anesthesia for operative procedures, as well as for ECT. Other agents that are frequently used for ECT include thiopental, ketamine, and etomidate.…”
mentioning
confidence: 99%
“…They found no difference between ketamine and methohexitone in relation to peak HR and SBP, whereas DBP was found to be higher among patients receiving ketamine. Rasmussen et al 13 found that blood pressurewas higher in the ketamine group than in the methohexitone group. Ketofol may provide a better haemodynamic stability compared with the ketamine alone.…”
Section: Discussionmentioning
confidence: 97%
“…A difference of at least six seconds of seizure duration between two groups was considered clinically significant as observed in a previous study 13 . For a power of 0.8 and α=0.05, a sample size of 11 patients in each group was required.…”
Section: Methodsmentioning
confidence: 99%
“…First, we utilized endotracheal intubation or a laryngeal mask in order to provide sufficient oxygenation and to prevent hypercapnia. Second, we selected remifentanil for anesthesia, because it has strong anti-nociceptive features and was expected to stabilize blood pressure [ 11 ]. Third, we had an NO appliance available in case of PH crisis.…”
Section: Discussionmentioning
confidence: 99%